PENGGUNAAN MEDIA PEMBELAJARAN PUISI UNTUK MENINGKATKAN APRESIASI SASTRA SISWA KELAS 9 F SMPN 02 PONTIANAK - Jesen; Maulidya Maharani; Zety; Ryandes Wahyudi; Saptiana Sulastri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to increase students' literary appreciation in poetry learning through the use of learning media. The method used is classroom action research (PTK) which is carried out in several cycles, including planning, implementation, observation and reflection. The research subjects were students of class IX F SMPN 02 Pontianak. Data collection techniques include observation, tests, and documentation. The results of the research show that the use of learning media can increase student activity, understanding of the content of poetry, and the ability to express interpretations. Apart from that, student learning outcomes also increase in each cycle. Thus, the use of learning media is effective in increasing students' literary appreciation in poetry learning.